2-Cinnamamido-4-Methylpentanamide and N-(2-Hydroxypropanoyl)Cinnamamide: Synthesis, Characterization, and Molecular Docking Studies Through PBP2a Protein - Rasyid, Herlina; Ernawati, Teni; Monoarfa, Indah Muthmainnah (Molekul, 2024)
ABSTRACT. Cinnamic acid has been found in several types of plants and has a diverse spectrum of bioactivity. Derivatization of cinnamic acid related to the improving bioactivity of a compound. Cinnamic acid can be found as an acid or in conjugated form with amides, esters, aldehydes. This research focus on the synthesis of amide derivatives of cinnamic acid to improve the bioactivity. Two compounds namely 2-cinnamamido-4-methylpentanamide (1a) and N-(2-hydroxypropanoyl)cinnamamide (1b) were carried out through amidation reaction using carbodiimide coupling reagent for 24 hours. The synthesized target compounds were characterized using FT-IR, GCMS-MS, 1H-NMR and 13C-NMR spectroscopy. The compounds were evaluated their antibacterial activity by molecular docking simulation against PBP2a (PDB ID: 1MWT) using AutoDock4 and AutoDockTools software. PBP2a is one of the main proteins in MRSA that has evolved to resist β-lactam antibiotics and was proposed to be the most likely target of MRSA. The inhibitory process of this protein works through inhibition of the bacterial cell wall. The synthesis process of 1a and 1b produced yields of 22.13% and 25.20%. Molecular docking results showed that 1a and 1b had better energy (ΔGbinding -7.33 and -6.29 kcal/mol) than Streptomycin as the control positive. The compounds of 1a and 1b had interactions on PBP2a through hydrogen bond with Asn464, Thr600, and Tyr519. This present study showed that the synthesized compounds from cinnamic acid derivatives have a potential to be used as antibacterial agents. Keywords: Amidation, antibacterial, 2-cinnamamido-4-methylpentanamide, molecular docking, N-(2-hydroxypropanoyl) cinnamamide.